Cesário, Disease and Medicine - Sobral do Rosário, Francisco (Portuguese Journal Internal Medicine, 2021)
Cesário Verde, a Portuguese poet of the 19th century, died at the age of 31 from tuberculosis. His short life was divided between poetic activity, barely recognized in life, and commercial activity. This work seeks to reflect on the role that the disease played in its poetic journey, the difficult relationship with Medicine and, finally, the importance that the doctor-patient relationship can assume.